Effect of Carbon Monoxide on Bacteria‐Stimulated Cytokine Production by Placental Explants. (13th September 2012) - Peltier, Morgan R.; Arita, Yuko; Gurzenda, Ellen M.; Klimova, Natalia; Koo, Hschi‐Chi; Murthy, Amitasrigowri; Hanna, Nazeeh
<x xml:space="preserve">Abstract</x> Problem Preterm birth is frequently caused by an inflammatory response to ascending infections of the reproductive tract. Carbon monoxide (CO) has potent anti‐inflammatory properties at subtoxic concentrations. Whether or not CO can modulate inflammatory responses by placental tissues is unclear. Methods Placental explant cultures were incubated with heat‐killed Escherichia coli or Ureaplasma parvum in the presence or absence of 250 ppm CO for 24 hr. Concentrations of cytokines relative viability of the cultures were quantified. Results Escherichia coli‐ and U. parvum‐stimulated IL‐1β production was significantly inhibited by CO supplementation. Escherichia coli‐stimulated, but not U. parvum‐stimulated, IFN‐γ production was inhibited by CO. While CO inhibited PGE2 production by unstimulated cells, no effects on bacteria‐stimulated prostaglandin production were detected. CO had no effect on basal or E. coli‐stimulated TNF‐α production but enhanced TNF‐α production by cultures stimulated with U. parvum. In addition, CO tended to improve the viability of the placental cultures. Conclusions Low concentrations of CO tended to reduce proinflammatory cytokines and to promote the production of anti‐inflammatory cytokines in a pathogen‐specific manner. These properties suggest that CO may be useful for promoting a pro‐pregnancy cytokine milieu by placental explants and may reduce the consequences of intrauterine infections.